The impact of somathopedical treatment of the Vital capacity with mild mentally and insufficiently developed pupils - Chichevska Jovanova, Natasha (Faculty of Philosophy, Skopje, 2000)
Our experience had the aim to sight the effect by the somatopedic treatment of the VK of our examiners. By the results from our research we can take the following conclusion: the use of experimental method made statistical progress on the vital capacity (VK) of easy mental insufficient development pupils.
Влијанието на соматопедскиот третман врз виталниот капацитет (VK) кај лесно ментално недоволно развиените ученици
Keywords: modify defectological diagnosis, modify defectological treatments, educational part of the treatment and modify test system II.